REKOMENDASI MODEL PENINGKATAN KEPATUHAN PENGELOLAAN KESEHATAN PASIEN GAGAL GINJAL TERMINAL DI RSUD dr. H. MOH. ANWAR SUMENEP - Elyk Dwi Mumpuningtias (Fakultas Ilmu Kesehatan, 2017)
Management of patients with end stage renal disease include physical therapy of the underlying disease, treatment of comorbid conditions, replace the renal function by renal replacement therapy. Compliance of health management on end stage renal diseases patients is required. Compliance consists of cognitive and psychomotor components. Cognitively, patient compliance involves understanding and ability to recall the information on medical advice. Compliance in hemodialysis patients affected by patient factors, health care systems and personel factor/provider. This study was observational design explanative aims to describe and analyzed the factors that affect the health management of compliance in patients with end stage renal disease. The population in this research was all patients with end stage renal disease who undergoing hemodialysis in the hemodialysis unit RSUD dr. H. Moh. Anwar Sumenep. Sampling technique used purposive sampling and obtained a sample of 32 patients in this study. Collecting data usedquestionnaires and was analyzed using partial least square (PLS). Measurement of inner model used to measure hypothesis with t statistic value > 1,96. The result showed that the t statistic value of patients factor was 1,989, health care system was 1,747 and provider factor was 2,933. The statistical result showed that factors of patient and personel factor/provider affected health management compliance. Improved health management compliance was required in patients with end stage renal disease, especially of patient factors required an understanding of the physical and psychological problems and patient motivation to comply. Enhanced compliance with health management approach based psychoeducation based on King interaction system will improve patient compliance of patients with end stage renal disease undergoing hemodialysis.